Preparation method of quasi-solid-state lithium ion battery composite polymer electrolyte membrane
A composite polymer electrolyte membrane using Al2O3 and SiO2 ceramic fillers with PVDF improves ionic conductivity and mechanical strength, addressing flammability and low conductivity issues in lithium-ion batteries, achieving high cycle stability.
Patent Information
- Application Number
- CN202411195440.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2024-12-17
AI Technical Summary
Current lithium-ion batteries face issues with flammability, low ionic conductivity, and mechanical weakness due to single polymer or inorganic solid electrolytes, limiting their large-scale application.
A method to prepare a quasi-solid-state lithium-ion battery composite polymer electrolyte membrane using Al2O3 and SiO2 ceramic fillers combined with PVDF polymer, enhancing mechanical strength and ionic conductivity by forming a composite polymer electrolyte material.
The composite electrolyte membrane exhibits high ionic conductivity and mechanical strength, maintaining 97.57% capacity retention after 200 cycles, suitable for lithium metal quasi-solid-state batteries.
Smart Images

Figure CN119153772A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solid-state lithium-ion battery materials, and in particular relates to a method for preparing a quasi-solid-state lithium-ion battery composite polymer electrolyte membrane. Background Art
[0002] Lithium-ion batteries stand out in new energy battery technology due to their advantages such as cleanliness, environmental protection, and high energy density. However, the lithium-ion batteries currently commercially available on the market are generally liquid electrolytes, which generally have safety issues such as flammability and explosion, which greatly limits their large-scale application. In addition, the electrolyte and diaphragm will occupy a large volume space in the battery, which limits the improvement of energy density in large-scale applications. The high energy density and high safety of solid-state lithium-ion batteries are considered to be the next generation of battery technology with great development potential, and are expected to fundamentally solve various problems of liquid lithium-ion batteries.
[0003] The rational use of solid electrolytes in lithium-ion batteries can effectively solve the problems of flammable and explosive electrolytes. As the core component of solid-state batteries, solid electrolytes determine the various performance parameters of solid-state batteries. An ideal solid electrolyte should have the advantages of high ionic conductivity, high chemical stability, excellent lithium ion transmission efficiency, and excellent mechanical strength. However, the ionic conductivity is low at room temperature, and Li + Factors such as small transfer number and poor mechanical strength limit the large-scale application of solid-state lithium-ion batteries.
[0004] Solid electrolytes can be divided into two categories: polymer solid electrolytes (SPEs) and inorganic solid electrolytes. It is difficult for single SPEs or inorganic solid electrolytes to meet general requirements such as sufficient ionic conductivity, high operating voltage, appropriate mechanical strength, and excellent interface contact. SPEs have good elasticity and adaptability to volume changes and are widely used in flexible batteries. However, polymers are easy to crystallize at low ambient temperatures, resulting in limited ionic conductivity, and their low compatibility with high-voltage cathode materials and poor mechanical properties cannot inhibit the growth of lithium dendrites, thereby deteriorating their electrochemical performance. Inorganic solid electrolytes have suitable ionic conductivity, a wide electrochemical window, and strong mechanical strength, but their brittleness and rigidity lead to poor processing performance of electrolyte materials and increased contact resistance between electrolyte materials and electrode materials. In recent years, researchers have been committed to integrating ceramic fillers into SPEs to form polymer / inorganic composite electrolytes (CPEs) to achieve the synergistic effect of different materials.
[0005] Ceramic fillers can not only improve the mechanical strength of the polymer matrix, but also act as plasticizers to prevent polymer crystallization and improve the ionic conductivity of solid electrolytes. In addition, the interaction between inorganic fillers and polymers also enhances the redox stability of the electrolyte, thereby broadening the electrochemical window of the battery and increasing the energy density of the battery to a certain extent. Therefore, a suitable inorganic filler and polymer electrolyte composite modification is needed, which has the advantages of good elasticity of SPEs and high ionic conductivity of inorganic solid electrolytes, wide electrochemical window and strong mechanical strength to meet the practical application of solid-state batteries. Summary of the invention
[0006] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a quasi-solid-state lithium-ion battery composite polymer electrolyte membrane, solve the problems of low lithium ion mobility and easy crystallization at room temperature existing in a single polymer electrolyte membrane, use raw materials composed of Al2O3 and SiO2 to prepare SiO2 ceramic filler and composite it with PVDF polymer to prepare a composite polymer solid electrolyte material, effectively suppressing the disadvantages of low mechanical strength and low lithium ion conductivity at room temperature when a single polymer is used as an electrolyte material.
[0007] To achieve the above object, the present invention is implemented through the following technical solutions:
[0008] A method for preparing a quasi-solid-state lithium-ion battery composite polymer electrolyte membrane comprises the following steps:
[0009] 1) Preparation of ceramic filler: 5-20 g of raw material X is kept in a muffle furnace at 300-800° C. for 3-9 h, the powder is taken out and dispersed into 1-3 L of 0.1-0.5 mol / L hydrochloric acid solution, and stirred for 30-90 min, the obtained suspension is allowed to stand for 1-5 h, and then the suspension is filtered with deionized water to obtain solid particles, and finally the solid particles are placed in a blast drying oven to dry to obtain ceramic filler;
[0010] 2) Preparation of solution A: PVDF and LiTFSI were mixed uniformly in a mass ratio of (2-2.8):1, then added into 10-30 ml of DMF solvent, and mixed and stirred for 4-9 hours to obtain solution A;
[0011] 3) Preparation of suspension B: Take 0.05-0.15 g of the ceramic filler obtained in step 1), add it to 10-30 ml of DMF solvent and perform ultrasonic treatment for 20-60 min to obtain suspension B.
[0012] 4) Slowly pour suspension B into solution A and continue stirring for 4 to 9 hours to mix evenly;
[0013] 5) Casting the suspension obtained in step 4) into a polytetrafluoroethylene mold, and vacuum drying in a vacuum drying oven at 50-60° C. for 12-36 hours, and peeling off the formed film after cooling to room temperature to obtain a composite polymer solid electrolyte material.
[0014] The chemical composition of the X raw material described in step 1) is Al2O3 and SiO2; the mass ratio of Al2O3 to SiO2 is (16-36):(52-65).
[0015] The X raw material is one or more of coal gangue and bauxite.
[0016] The molecular weight of the PVDF described in step 2) is 400,000 to 650,000.
[0017] The particle size of the X raw material described in step 1) is 100-300 nm.
[0018] The drying temperature in the blast drying oven in step 1) is 70-90°C.
[0019] The amount of LiTFSI in step 2) is 0.1-0.5 g.
[0020] The polytetrafluoroethylene mold described in step 5) is circular or rectangular.
[0021] The thickness of the film is 100-150 μm.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The preparation method of ceramic fillers in composite polymer electrolyte membranes is relatively simple. Compared with commercial ceramic fillers on the market, they are low-cost and widely available. They can be obtained from waste in coal mines, which increases their added value and helps achieve carbon neutrality.
[0024] 2. The X raw material is subjected to a simple annealing treatment to obtain a ceramic filler, which can reduce the crystallinity of PVDF at room temperature and improve the ionic conductivity.
[0025] 3. This composite polymer solid electrolyte is used in lithium metal quasi-solid-state batteries. Under the test conditions of temperature of 30°C and current density of 0.3C (172mA / g), the capacity retention rate is still 97.57% after 200 cycles, which shows that this polymer solid electrolyte has considerable application prospects in the field of lithium metal quasi-solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a preparation flow chart of composite solid electrolyte.
[0027] Figure 2This is the XRD diagram of the composite solid electrolyte of Example 3.
[0028] Figure 3 This is an electrochemical window test diagram of the composite solid electrolyte of Example 3.
[0029] Figure 4 This is a test graph of the ionic conductivity of the composite solid electrolyte of Example 3.
[0030] Figure 5 This is a long cycle test diagram of the assembled LiFePO4||Li full battery of the composite solid electrolyte in Example 3. DETAILED DESCRIPTION
[0031] The present invention is described in detail below in conjunction with the accompanying drawings, but it should be noted that the implementation of the present invention is not limited to the following embodiments.
[0032] A method for preparing a quasi-solid-state lithium-ion battery composite polymer electrolyte membrane comprises the following steps:
[0033] 1) Preparation of ceramic filler: 5-20 g of raw material X (particle size of 100-300 nm) is kept in a muffle furnace at 300-800° C. for 3-9 h, the powder is taken out and dispersed into 1-3 L of 0.1-0.5 mol / L hydrochloric acid solution, and stirred for 30-90 min. The obtained suspension is allowed to stand for 1-4 h, and then the suspension is filtered with deionized water to obtain solid particles, and finally the solid particles are placed in a blast drying oven for drying (70-90° C.) to remove excess water, thereby obtaining a ceramic filler (CP); the chemical composition of raw material X is Al2O3 and SiO2; the mass ratio of Al2O3 to SiO2 is (16-36):(52-65). Raw material X can be one or more of coal gangue and bauxite.
[0034] 2) Preparation of solution A: polyvinylidene fluoride (PVDF) and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) were mixed uniformly in a mass ratio of (2-2.8):1, and then added into 10-20 ml of DMF solvent, and mixed and stirred for 4-9 hours to obtain solution A; the molecular weight of PVDF was 400000-650000. Among them, the amount of LiTFSI was 0.1-0.5 g.
[0035] 3) Preparation of suspension B: Take 0.05-0.15 g of the ceramic filler obtained in step 1), add it to 10-20 ml of N,N-dimethylformamide (DMF solvent), and ultrasonicate for 20-60 min to obtain suspension B.
[0036] 4) Slowly pour suspension B into solution A and continue stirring for 4 to 9 hours to mix evenly;
[0037] 5) Casting the suspension obtained in step 4) into a polytetrafluoroethylene circular mold with a diameter of 40 to 70 mm, and vacuum drying in a vacuum drying oven at 50 to 60° C. for 12 to 36 hours, and peeling off the formed film (thickness of 100 to 150 μm) after cooling to room temperature to obtain a composite polymer solid electrolyte material.
[0038] Example 1
[0039] See Figure 1 , a method for preparing a composite polymer electrolyte membrane for a quasi-solid-state lithium-ion battery, first, take 10g of X raw material (the mass ratio of Al2O3 and SiO2 is 35:65) with a particle size of less than 200nm in a muffle furnace at 600℃, keep warm for 5h, and take out the powder. Then measure 9ml of hydrochloric acid with a concentration of 12mol / L and dissolve it in 1L of deionized water, add the powder and stir for 60min, then let the suspension stand for 2h, filter the suspension to obtain solid particles, wash the solid particles with water 4 times until neutral, place the solid particles in a blast drying oven, and blast dry them at 80℃ overnight to obtain CP. Then weigh 0.07g, 0.8g and 0.3g of CP, PVDF and LiTFSI respectively, and place them in a vacuum drying oven at 60℃ and dry them for 24h. Take out the treated PVDF and LiTFSI, add 15ml of DMF, mix and stir for 6h to obtain solution A. Take out the treated CP, add 10ml of DMF and ultrasonicate for 30min to obtain suspension B. The suspension B was slowly poured into the solution A and stirred for 6 hours to mix well. The suspension was cast into a polytetrafluoroethylene mold with a diameter of 60 mm, vacuum dried at 55°C for 24 hours, and the film was peeled off to obtain a composite polymer electrolyte membrane with a thickness of 110 μm.
[0040] Example 2
[0041] See Figure 1, a method for preparing a composite polymer electrolyte membrane for a quasi-solid-state lithium-ion battery, first, take 10g of X raw material (the mass ratio of Al2O3 and SiO2 is 35:65) with a particle size of about 200nm, heat it in a muffle furnace at 600℃, keep it warm for 5h, and take out the powder. Then, measure 9ml of hydrochloric acid with a concentration of 12mol / L and dissolve it in 1L of deionized water, add the powder and stir for 60min, then let the suspension stand for 2h, filter the suspension to obtain solid particles, wash the solid particles with water 4 times until neutral, place the solid particles in a blast drying oven, and blast dry them at 80℃ overnight to obtain CP. Then weigh 0.1g, 0.8g and 0.3g of CP, PVDF and LiTFSI respectively, place them in a vacuum drying oven at 60℃ and dry them for 24h. Take out the treated PVDF and LiTFSI, add 20ml of DMF, mix and stir for 6h to obtain solution A. Take out the treated CP, add 15ml of DMF and ultrasonicate for 30min to obtain suspension B. The suspension B was slowly poured into the solution A and stirred for 6 hours to mix well. The suspension was cast into a polytetrafluoroethylene mold with a diameter of 60 mm, vacuum dried at 55°C for 24 hours, and the film was peeled off to obtain a composite polymer electrolyte membrane with a thickness of 115 μm.
[0042] Example 3
[0043] See Figure 1 , Preparation method of quasi-solid-state lithium-ion battery composite polymer electrolyte membrane, first, take 10g of X raw material (mass ratio of Al2O3 and SiO2 is 35:65) with a particle size of about 200nm, heat it in a muffle furnace at 600℃, keep it warm for 5h, and take out the powder. Then measure 9ml of hydrochloric acid with a concentration of 12mol / L and dissolve it in 1L of deionized water, add the powder and stir for 60min, then let the suspension stand for 2h, filter the suspension to obtain solid particles, wash the solid particles with water 4 times until neutral, place the solid particles in a blast drying oven, and blast dry them at 80℃ overnight to obtain CP. Then weigh 0.15g, 0.8g and 0.3g of CP, PVDF and LiTFSI respectively, place them in a vacuum drying oven at 60℃ and dry them for 24h. Take out the treated PVDF and LiTFSI, add 25ml of DMF, mix and stir for 6h to obtain A solution. Take out the treated CP, add 20ml of DMF and ultrasonicate for 30min to obtain B suspension. The suspension B was slowly poured into the solution A and stirred for 6 hours to mix well. The suspension was cast into a polytetrafluoroethylene mold with a diameter of 60 mm, vacuum dried at 55°C for 24 hours, and the film was peeled off to obtain a composite polymer electrolyte membrane with a thickness of about 120 μm.
[0044] Example 4.
[0045] See Figure 1, Preparation method of quasi-solid-state lithium-ion battery composite polymer electrolyte membrane, first, take 10g of coal gangue in a muffle furnace at 700℃, keep warm for 3h, and take out the powder. Then measure 10ml of hydrochloric acid with a concentration of 12mol / L and dissolve it in 1L of deionized water, add the powder and stir for 60min, then let the suspension stand for 5h, filter the suspension to obtain solid particles, wash the solid particles 4 times with water until neutral, place the solid particles in a blast drying oven, and blow dry them at 80℃ overnight to obtain a ceramic filler named MGS. Then weigh 0.15g, 0.8g and 0.3g of MGS material, PVDF and LiTFSI respectively, and place them in a vacuum drying oven at 60℃ for 24h. Take out the treated PVDF and LiTFSI, add 25ml of DMF, mix and stir for 6h to obtain solution A. Take out the treated MGS material, add 20ml of DMF and ultrasonicate for 30min to obtain suspension B. Slowly pour suspension B into solution A, stir for 6h, and mix evenly. The suspension was cast into a polytetrafluoroethylene mold with a diameter of 60 mm, vacuum dried at 55° C. for 24 h, and the film was peeled off to obtain a composite polymer electrolyte membrane with a thickness of about 120 μm.
[0046] Example 5
[0047] See Figure 1 , Preparation method of quasi-solid-state lithium-ion battery composite polymer electrolyte membrane, first, take 10g of bauxite in a muffle furnace at 500℃, keep warm for 4h, and take out the powder. Then measure 20ml of hydrochloric acid with a concentration of 12mol / L and dissolve it in 1L of deionized water, add the powder and stir for 60min, then let the suspension stand for 4h, filter the suspension to obtain solid particles, wash the solid particles with water 4 times until neutral, place the solid particles in a blast drying oven, and blow dry them at 80℃ overnight to obtain a ceramic filler named LTK. Then weigh 0.15g, 0.8g and 0.3g of LTK material, PVDF and LiTFSI respectively, place them in a vacuum drying oven at 60℃ and dry them for 24h. Take out the treated PVDF and LiTFSI, add 25ml of DMF, mix and stir for 6h to obtain solution A. Take out the treated LTK material, add 20ml of DMF and ultrasonicate for 30min to obtain suspension B. Slowly pour suspension B into solution A, stir for 6h, and mix evenly. The suspension was cast into a polytetrafluoroethylene mold with a diameter of 60 mm, vacuum dried at 55° C. for 24 h, and the film was peeled off to obtain a composite polymer electrolyte membrane with a thickness of about 120 μm.
[0048] The assembly process of solid-state lithium-ion batteries, including the preparation of electrode sheets and the process of assembling lithium solid-state batteries, is as follows:
[0049] Lithium iron phosphate, conductive agent (Super-P), and binder (PVDF) were weighed in a mass ratio of 8:1:1, ground and mixed evenly, N-methylpyrrolidone (NMP) was added to form a viscous slurry, and then evenly coated on the surface of the current collector (aluminum foil) with a coater.
[0050] Place the aluminum foil coated with the slurry in a vacuum oven at 120°C and bake for 12 hours to remove the NMP solvent. Finally, cut the aluminum foil into circular positive electrode sheets with a diameter of 11 mm for use. The composite polymer electrolyte membrane is cut into discs with a diameter of 15.6 mm. The order of encapsulating the battery is as follows: negative electrode shell, lithium sheet, diaphragm, positive electrode sheet, gasket, spring sheet, positive electrode shell. During the assembly process, 6 microliters of lithium battery electrolyte are dripped on the surface of the composite polymer electrolyte membrane. The entire process of encapsulating lithium metal solid-state batteries is carried out in a glove box filled with argon, and the water and oxygen contents are less than 0.1 ppm.
[0051] Table 1
[0052]
[0053] Table 1 is a comparison of the long cycle test of the assembled LiFePO4||Li full battery of the composite solid electrolyte of Examples 1, 2, 3, 4, and 5. Their first cycle discharge specific capacities are 176.56mAh / g, 167.00mAh / g, 175.87mAh / g, 171.06mAh / g, and 165.35mAh / g, respectively, and the capacity retention rates of the 200th cycle are 10.10%, 96.85%, 97.57%, 96.26%, and 95.86%, respectively, indicating that the ceramic filler prepared by this method, when filled into the composite solid electrolyte, exhibits good cycle stability. And materials such as coal gangue and bauxite with Al2O3 and SiO2 as the main components also have relatively excellent electrochemical properties after being treated by the method of the present invention.
[0054] Depend on Figure 2 It can be seen that the XRD spectrum of the ceramic filler (CP) corresponds to the standard card PDF#46-1045, which proves that the main component of the filler is SiO2, and after the ceramic filler is filled and modified in the PVDF solid electrolyte, the crystallinity of PVDF is reduced, which is beneficial to the conduction of lithium ions by the solid electrolyte.
[0055] Depend on Figure 3 It can be seen that the oxidative decomposition potential of the composite solid electrolyte is 5.0 V. The higher oxidative decomposition potential has a wider stability electrochemical window for metallic lithium, which can meet the application requirements of high-voltage lithium batteries.
[0056] Depend on Figure 4 It can be seen that when the temperature is 30°C, the ionic conductivity of the composite solid electrolyte is 4.342×10-4 The reason for the higher ionic conductivity may be that the CP filler inhibits the further crystallization of the polymer chain and increases the internal amorphous phase region of the electrolyte, which is consistent with the XRD result of Example 3.
[0057] Depend on Figure 5 It can be seen that the discharge capacity of the full battery in the first cycle under the test conditions of 0.3C current density and 30°C is 175.87mAh / g, and the capacity retention rate is 97.57% after 200 cycles.
Claims
1. A method for preparing a quasi-solid-state lithium-ion battery composite polymer electrolyte membrane, characterized in that: The following steps are involved: 1) Preparation of ceramic filler: 5-20 g of raw material X is kept in a muffle furnace at 300-800° C. for 3-9 h, the powder is taken out and dispersed into 1-3 L of 0.1-0.5 mol / L hydrochloric acid solution, and stirred for 30-90 min, the obtained suspension is allowed to stand for 1-5 h, and then the suspension is filtered with deionized water to obtain solid particles, and finally the solid particles are placed in a blast drying oven to dry to obtain ceramic filler; 2) Preparation of solution A: PVDF and LiTFSI were mixed uniformly in a mass ratio of (2-2.8):1, then added into 10-30 ml of DMF solvent, and mixed and stirred for 4-9 hours to obtain solution A; 3) Preparation of suspension B: Take 0.05-0.15 g of the ceramic filler obtained in step 1), add it to 10-30 ml of DMF solvent and perform ultrasonication for 20-60 min to obtain suspension B; 4) Slowly pour suspension B into solution A and continue stirring for 4 to 9 hours to mix evenly; 5) Casting the suspension obtained in step 4) into a polytetrafluoroethylene mold, and vacuum drying in a vacuum drying oven at 50-60° C. for 12-36 hours, and peeling off the formed film after cooling to room temperature to obtain a composite polymer solid electrolyte material.
2. The method for preparing a quasi-solid-state lithium-ion battery composite polymer electrolyte membrane according to claim 1, characterized in that: The chemical composition of the X raw material described in step 1) is Al2O3 and SiO2; the mass ratio of Al2O3 to SiO2 is (16-36):(52-65).
3. The method for preparing a quasi-solid-state lithium-ion battery composite polymer electrolyte membrane according to claim 1, characterized in that: The X raw material is one or more of coal gangue and bauxite.
4. The method for preparing a quasi-solid-state lithium-ion battery composite polymer electrolyte membrane according to claim 1, characterized in that: The molecular weight of the PVDF described in step 2) is 400,000 to 650,000.
5. The method for preparing a quasi-solid-state lithium-ion battery composite polymer electrolyte membrane according to claim 1, characterized in that: The particle size of the X raw material described in step 1) is 100-300 nm.
6. The method for preparing a quasi-solid-state lithium-ion battery composite polymer electrolyte membrane according to claim 1, characterized in that: The drying temperature in the blast drying oven in step 1) is 70-90°C.
7. The method for preparing a quasi-solid-state lithium-ion battery composite polymer electrolyte membrane according to claim 1, characterized in that: The amount of LiTFSI in step 2) is 0.1-0.5 g.
8. The method for preparing a quasi-solid-state lithium-ion battery composite polymer electrolyte membrane according to claim 1, characterized in that: The polytetrafluoroethylene mold described in step 5) is circular or rectangular.
9. The method for preparing a quasi-solid-state lithium-ion battery composite polymer electrolyte membrane according to claim 1, characterized in that: The thickness of the film is 100-150 μm.
Citation Information
Cited By
Solid electrolyte and preparation method thereof
CN119764549A
